2018
DOI: 10.24193/subbchem.2018.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Soils in the Almasu Mare Area through the Determination of Lead Concentrations

Abstract: The present study consisted in the determination of lead concentrations in soil samples and sterile material dumped collected from the Almașu Mare mining area. The lead concentration in the samples collected were determined by atomic adsorption spectrometry (AAS). In spite of the fact that all mines from area are nowadays inactive, the results of the chemical analysis showed that the soils in the area are still highly polluted with lead, except at the base of the "Radeș" dump, where the lead concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It involves reducing Pb metallic element through different chemical additives such as zeolite, activated carbon, steel slag, clay, red mud, carbide slag, sand, lime, and cement [ 182 , 183 ]. However, it was also reported that cement and lime were effective in immobilization of Pb in artificially Pb-contaminated soil samples, while clay, activated carbon, sand, and zeolite were not effective in those soil samples [ 184 ]. Ge, Jiang [ 185 ] conducted an experiment to observe the stabilization/solidification of high Pb-contaminated soils using insoluble porous, neutral, and green material (humin) extracted from natural peat soils and found that humin reduced the bioavailability and mobility of Pb metallic ions due to its high adsorbent capacity, [ 185 ].…”
Section: Promising Remediation Strategies To Reduce Pb Toxicity In So...mentioning
confidence: 99%
“…It involves reducing Pb metallic element through different chemical additives such as zeolite, activated carbon, steel slag, clay, red mud, carbide slag, sand, lime, and cement [ 182 , 183 ]. However, it was also reported that cement and lime were effective in immobilization of Pb in artificially Pb-contaminated soil samples, while clay, activated carbon, sand, and zeolite were not effective in those soil samples [ 184 ]. Ge, Jiang [ 185 ] conducted an experiment to observe the stabilization/solidification of high Pb-contaminated soils using insoluble porous, neutral, and green material (humin) extracted from natural peat soils and found that humin reduced the bioavailability and mobility of Pb metallic ions due to its high adsorbent capacity, [ 185 ].…”
Section: Promising Remediation Strategies To Reduce Pb Toxicity In So...mentioning
confidence: 99%